Penerapan Sistem Informasi Posyandu Berbasis Website Pada Posyandu Warga Nglejok Rw 15 - Pratama, Rizki Yonda; Maharani, Rizkysari Mei; Murti, Alif Catur (SAFE-Network, 2024)
Posyandu (Integrated Healthcare Post) is a routine activity that plays a crucial role in supporting community health, particularly for mothers and children. However, the activities at posyandu Warga Nglejok RW 15, named Teratai1, still face challenges in managing data and recording activity outcomes, which are carried out manually using notebooks. This manual system tends to be time-consuming, prone to errors, and inefficient in storage and report generation. Therefore, a solution is needed in the form of implementing a web-based information system to simplify data and information management related to posyandu activities. The information system, named Si Paling is designed to include features such as participant registration, recording health data for mothers and children, and managing activity schedules. The development method uses the waterfall approach, which includes the stages of analysis, design, implementation, testing, and maintenance. The implementation results are expected to demonstrate that the system can enhance efficiency, accuracy, and ease of data access for posyandu facilitators. With this system, administrative processes become more structured, data is more secure, and reports can be generated quickly. This information system is expected to provide a sustainable solution to support the digitalization of Posyandu services and improve community health quality in the Nglejok RW 15 area.